"Importance of children short stories in the process of teaching and learning english in the general basic education - Martínez, Isabel (David, Panamá : UDELAS, 2011)
The research, has as purpose to offer some elements of enough judgments in order to be consider as a methodology to achieve the english language teaching-learning process.
GENERAL INDEX INDEX OF CHARTS INDEX OF GRAPHICS INTRODUCTION CHAPTER I: OVERVIEW OF THE RESEARCH CHAPTER II: THEORICAL FRAMEWORK 2.1. The short story: origins, history, definitions 2.2. Classification of short stories, elements, structure, techniques and style 2.3. Contions to be met by children's stories 2.4. The educational role of the story 2.5. Processing of learning orientation 2.5.1. Education of perception 2.5.2. Exercising intuition 2.5.3. Criticism orientation 2.5.4. Stimulating creativity 2.5.5. Teaching expresssiveness 2.6. Story telling in teaching foreign languages 2.7. The stories in language teaching: understanding and transformation 2.8. The teacher as a storyteller CHAPTER III: METHODOLOGY CHAPTER IV: ANALYSIS OF RESULT CHAPTER V: CONCLUSION AND RECOMENDATION BIBLIOGRAPHY ANNEX
Incluye Indice General
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés.
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: LENGUAJE Y LENGUAS -- TESIS DE LICENCIATURA -- ENSEÑANZA -- MÉTODO BILINGÜE; ENGLISH -- TESIS DE LICENCIATURA -- TEACHING; FACULTAD DE CIENCIAS SOCIALES; ESCUELA DE INGLÉS; LICENCIATURA EN DOCENCIA EN INGLÉS; SHORT STORIES